NETWORK NODE INTRUSION DETECTION SYSTEM - Yousif, Abeer; Fawzy, Suleiman (Iraqi Journal of Science, 2024)
Computer network technologies have grown rapidly in the last few decades. With the increased use of networked computers for critical applications, computer intrusions have been increased and became a significant threat to these systems and, thus Intrusion Detection Systems (IDS) have become essential addition to security infrastructure of most organizations. This paper presents the design and implementation of a Network Node Intrusion Detection System (NNIDS) that support IPv4 protocol. It detects a variety of attacks which are directed to the resources of filing system. The implied detection rules are based on matching the predefined normal behavior of the system with the characteristics of the detected user’s events.Several simulated attacks have been sent to the proposed system to test it. Test shows that most of the attacks can be detected with acceptable ratios of false positive and false negative values.